On the nature of catastrophic forms - Petryna, Adriana; Mitchell, Paul Wolff (BioSocieties, 2017)
The impact of humans on the Earth’s ecosystem has led to the declaration of a new geological era, the Anthropocene. Earth systems stable for millennia are now threatened by anthropogenic climate change, but this pending instability is not well understood. Researchers from varied disciplines have assembled conceptual toolkits of “abrupt change” science to theorize and model nonlinear shifts. We offer a genealogy of these toolkits, tracing them back to the early and mid-twentieth century problematic of morphogenesis, or the development and evolution of organic form. Mathematician René Thom, inspired by iconoclastic biologists D’Arcy Thompson's and Conrad Hal Waddington’s studies of growth and form, formalized his so-called catastrophe theory in the 1970s. This theory not only purported to explain abrupt change in complex systems, but also presented a novel heuristic of a “nature” of catastrophic form. Thom’s catastrophe theory was applied as a method of thought in the physical, social, and life sciences, but waned after criticism. However, as elements of this theory recycle into today’s abrupt change science, the nature of catastrophic form assumes importance in a scientific imaginary’s response to ecosystemic behaviors that are not subject to, or do not even correspond to, conventional expectations about the future.